Captain Underpants and the wrath of the wicked wedgie woman : the fifth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2001)
George and Harold have really done it this time--They've created a monster! She's faster, smarter, and more evil than anything the world has seen before--she's Wedgie Woman! With the help of her horrible robots and her horrendous hairdo, Wedgie Woman is on a mission to take over the world, and she'll give a whopping wedgie to anyone who stands in her way--including Captain Underpants.
Ages 7-10
RL 3
640
Accelerated Reader AR
Keywords: Schools -- Juvenile fiction; School principals -- Juvenile fiction; Heroes -- Juvenile fiction; Cartoons and comics -- Juvenile fiction; Humorous fiction